2004
DOI: 10.1128/jcm.42.4.1609-1613.2004
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Group A Human Rotavirus Types Circulating over a 4-Year Period in Madrid, Spain

Abstract: The incidence and distribution of human rotavirus G types among children under 5 years old with acute gastroenteritis were determined over a 4-year period (1998 to 2002) by using monoclonal antibodies and reverse transcription-PCR methods. Rotavirus was detected in 1,155 (31%) of 3,760 specimens tested. Rotavirus was studied in every month of the 48-month survey period. Rotavirus activity occurred mainly (51%) in the typically cooler months in Spain (November to February). The age distribution of rotavirus-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
35
0
5

Year Published

2004
2004
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 41 publications
6
35
0
5
Order By: Relevance
“…In general, all recent studies confirm that the diversity of rotavirus strains is much greater than previously recognized (8,14,15,21,42).…”
Section: Discussionsupporting
confidence: 63%
“…In general, all recent studies confirm that the diversity of rotavirus strains is much greater than previously recognized (8,14,15,21,42).…”
Section: Discussionsupporting
confidence: 63%
“…This was the first study to investigate the role of currently recognized viruses, especially NoVs, sapoviruses, and Aichi viruses, in infections of children. As was the case in a previous study (36), this two-year surveillance also showed that the vast majority (75.8%) of the children with gastroenteritis were less than 2 years old. Almost half of the infections (43.7%) were due to one or several viral agents, mainly to RVs and NoVs.…”
Section: Discussionsupporting
confidence: 50%
“…While between 1985 and 2004, G2P [4], G4P [8], and G9P [8] strains varied in their distribution or completely disappeared for short or long periods of time, G1 strains have been continuously circulating in the infant population of Palermo, a pattern that has been described in various other geographical settings as well (6,9,11,25,35,46,58,59). However, unlike the G2P [4] and G4P [8] Italian rotavirus strains, a highly heterogeneous population of G1 strains has been circulating in Italy over the whole study period.…”
Section: Discussionmentioning
confidence: 92%